Tugas Pendidik Kristen dalam Melaksanakan Pencegahan Pernikahan di Bawah Umur Bagi Remaja Kristen di Kabupaten Sanggau Kalimantan Barat - Gianto Gianto; Marthen Mau (Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
Marriage and marriage must be positioned as something sacred because it is needed to prevent early marriage. The implementation of marriage at a young age is influenced by economic factors, poverty, the effects of bad relationships, premarital sex, and spiritual maturity. This article aims to prevent underage marriage for Christian teenagers. This article uses qualitative methods through observation, interviews and literature studies. This study shows that if Christian educators are more diligent in implementing the prevention of underage marriage, then Christian teenagers will increasingly understand that marriage and marriage are God's gifts that are only allowed for everyone who has experienced adulthood. Conclusion; marriage and marriage are God's gifts that must be carried out when each person has experienced physical, intellectual, social, emotional, moral and spiritual maturity.